KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA MTsN PEUREUMEU KABUPATEN ACEH BARAT - Syamsul Bahri; Nasir Usman; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The performance of principals is a crucial factor in improving the competence of educator professional as well as teachers. This observation is intended to let us know the steps taken in devising plans and strategies and obstacles found by leaders in schools for teacher professional enhancement on Madrasah Tsanawiyah Negeri  Peureumeu Aceh Barat Regency. This observation uses exposure method with qualitative approach. Observation techniques, interviews, documentation and triangulation performed for data collection. Study subjects were school leaders, vice principals, MGMP leaders, and educators as well as teachers. The study results showed that: (1) The ability of school leaders to be taken in developing professional teacher improvement plans is to identify problems, analyze challenges and solve them, programming, formulating activities and formulating cost plans; (2) Strategies implemented by school leaders to improve the competence of teaching professionals as well as educators are using the stage of creating work programs, establishing and activating MGMP activities in schools, education and training, and giving permission to continue higher education; (3) Obstacles encountered in improving the professional competence of teachers is limited availability of facilities, time constraints, responsibilities sebahagian teachers who are still low and cost limitations. Keywords: Principals' Performance and Teacher Professional Competence.